Implementation of 21st Century Learning: A Review of Teachers' Ability to Design and Implement Learning - Husnaini Bahri; Eva Moy Wonley; Monica Hetharia (Journal of Biological Science and Education, 2025)
This study aims to examine the alignment between the planning and implementation of biology learning based on the 2013 Curriculum in public high schools in Biringkanaya District, Makassar City, with a focus on the integration of 4C skills and Higher-Order Thinking Skills (HOTS). This study uses mixed methods involving four 11th grade biology teachers. Data were collected through analysis of lesson plans, observation of classroom teaching, and teacher questionnaires, then analyzed descriptively and inferentially using the chi-square test. The results showed that the quality of lesson plan preparation and biology teaching implementation was generally very low, especially in the formulation of Competency Achievement Indicators and learning objectives, which were still dominated by low-level thinking skills (C1–C2). The observation results also revealed limitations in the use of authentic stimuli, HOTS questions, and meaningful discussions, so that the development of students' 4C and HOTS skills was not optimal. The chi-square test showed a significant relationship between teachers' ability to design lesson plans and the quality of classroom teaching. These results emphasize the importance of strengthening teachers' pedagogical competencies in designing and implementing biology learning that is aligned with and oriented towards 21st-century skills.Keywords: lesson plans, learning implementation, biology.